“Alle Hilfsmittel an der Hand”: note sulle prime fotografie collezionate da Aby Warburg - Mazzucco, Katia (Rivista di studi di fotografia. Journal of Studies in Photography, 2020)
There is no evidence of a consistent theoretical position of Aby Warburg regarding photography, but his scattered notes on the subject allow for a deductive evaluation. The considerable use of photographs that he made in his work suggests a wide range of methodological approaches, with significant implications for the disciplinary and methodological definition of art history and the development of photographic documentation at the turn of the 20th century. This essay provides examples of Warburg’s early attention to photography, both as a research tool and a required piece of equipment for any research institute.